1983
DOI: 10.1002/ijc.2910310310
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity during mouse hepatitis virus infection: Response in the absence of interferon

Abstract: The ability of the JHM3 strain of mouse hepatitis virus (MHV) to induce natural killer (NK) cells was examined. Infection of C57BL/6 (B6) mice with this virus resulted in the augmentation of natural cytotoxicity against YAC-I target cells in the absence of a detectable interferon response. The cells responsible for this increased cytotoxicity were sensitive to complement-mediated lysis with an anti-Q-5 reagent but not with a Thy 1.2 antiserum, indicating that they possess an NK-like surface phenotype. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…There have been few reports regarding IFN induction by MHV strains. MHV-JHM did not induce IFN in cultured neuronal cells (27) or in the spleens of mice injected intraperitoneally or intracranially (29). However, MHV-3 given to mice intraperitoneally did induce detectable IFN in the spleen (21,29).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There have been few reports regarding IFN induction by MHV strains. MHV-JHM did not induce IFN in cultured neuronal cells (27) or in the spleens of mice injected intraperitoneally or intracranially (29). However, MHV-3 given to mice intraperitoneally did induce detectable IFN in the spleen (21,29).…”
Section: Discussionmentioning
confidence: 86%
“…MHV-JHM did not induce IFN in cultured neuronal cells (27) or in the spleens of mice injected intraperitoneally or intracranially (29). However, MHV-3 given to mice intraperitoneally did induce detectable IFN in the spleen (21,29). Because of the difficulty associated with interpreting results of studies in which different host systems or routes of inoculation were used, we have done a systematic study of the in vitro capacities of several MHV strains to induce 1FN production in several host types.…”
Section: Discussionmentioning
confidence: 99%
“…NK-sensitive YAC-1 target cells were labelled with 100 /~Ci sodium 5aCr (DuPont NEN Research Products, Boston, MA, U.S.A.) and incubated with spleen or brain-derived mononuclear cells at various effector: target (E:T) ratios for 4 h at 37°C in microtiter plates as described previously (Stohlman et al, 1983). Spontaneous release was determined by incubating medium with targets for 4 h. Maximum 51Cr release was determined by adding 0.25% Triton X-100 to target cells.…”
Section: Assay For Nk Activitymentioning
confidence: 99%
“…In other studies, adoptive transfer of nylon wool-adherent CD4+ T cells was shown to effect viral clearance in infected mice; elimination of CD8+ cells from the recipient abrogated this effect, suggesting that both CD4+ and CD8+ cells were required for maximal effect . In addition, cytotoxic B cells and NK-like cells may have a role in the host immune response to MHV (Stohlman et al, 1983;Welsh et al, 1986;Carman et al, 1986).…”
Section: Introductionmentioning
confidence: 99%